Easing of Regulatory Barriers to Telemedicine Abortion in Response to COVID-19 - Skuster, Patty; Dhillon, Jina; Li, Jessica (Frontiers in Global Women's Health, 2021)
For many people seeking abortion during the continuing COVID-19 pandemic, telemedicine abortion is the safest and most acceptable method, posing lower risk of exposure to the virus. In addition, by reducing in-person visits with health care providers, increased use of telemedicine for abortion can reduce pressure on overburdened health systems. Given the benefits of telemedicine during the pandemic, government agencies in several countries took measures to temporarily allow telemedicine abortion. We conducted key-word English-language searches to identify examples of government action to remove regulatory barriers to the practice of telemedicine abortion in response to the pandemic. We found instances of government agencies in eight countries taking steps to ease regulatory barriers to telemedicine abortion. Telemedicine abortion is safe, cost-effective, and may be the preferred method of abortion during acute periods of COVID-19 transmission, as well as after the pandemic has abated. As one step to expanding access to abortion with medicine where abortion is legal, health agencies and other regulatory bodies can take steps to remove barriers specific to telemedicine abortion.